The problem of personal identity in Critique of Pure Reason § 16 - Bonaccini, Juan Adolfo (Estudios de Filosofía, 2009)
Most readers of the first Critique often account for Kant ́s Transcendental Deduction of the Categories (TDC) as an answer to the problem of causation established by Hume. But not all of them seem to be aware, however, that the TDC is also a reply to Hume`s challenge to the notion of Personal Identity. To make this clear, the author suggests that, first of all, Hume’s attack on Personal Identity is addressed to the supposed Substantiality of the Cartesian Subject rather than to the Lockean Ego, and second that Hume tackles its supposed numerical identity. Then, the author claims that Kant redefines, in the first part of TDC, the Numerical Identity of Ego rather in Logical than in Substantial Terms and reconstructs his argument against Hume`s challenge. Finally, Kant ́s conception of Logical Unity and Identity of Self-consciousness is presented and discussed in general terms.